Impact of Successful Choanal Atresia Repair on the Nasal Mucosa: A Preliminary Study - Elsheikh,Ezzeddin (2017)
Abstract Introduction Themain histological features of the nasalmucosa in choanal atresia are distorted cilia, marked increase of mucous submucosal glands associated with marked reduction of goblet cell density, and lymphocytic cellular infiltration. Objective To study the nasal mucosal changes in cases of choanal atresia after successful repair compared with pre-repair mucosal histological features. Methods Tissue samples were taken from the inferior turbinate of 3 patients (1 bilateral and 2 unilateral) who were successfully operated. Then, the biopsies were subjected to histopathological, histochemical and immunohistochemical studies. After that, the results were compared with pre-repair findings in the choanal atresia side and in the normal side. Results Four biopsies (4 repaired choanal atresia sides) of the mucosa of the inferior turbinate revealed that 1 patient (who had a bilateral choanal atresia repaired), after achieving a patent choana for 8 months, had not completely recovered a normal nasal mucosa. The other 2 patients, after 18 and 23 months of achieving a patent choana, showed normal nasal cavities. Conclusion The main histological features of the nasal mucosa in choanal atresia could be reversed by surgery, making the patients regain their choanal patency, with their mucosae changing back to normal gradually with time.